Elementary Education through KGBVs— A Case Study - MISHRA, PATANJALI (THE PRIMARY TEACHER, 2015)
Education is related to our existence. Denial of education is related with denial of living. Education is a basic human right that increases the economic, social and political opportunities available to an individual. The state of elementary education in India is dismal. Government is taking every possible step but still we are not able to consolidate over the efforts. Keeping in view the dilapidated condition of elementary education of girls, among these, National Programme for Education of Girls at Elementary Level (NPEGEL), Mahila Samakhya (MS) and Kasturba Gandhi Balika Vidhyalaya (KGBV) are prominent, which are running across the country. KGBV is a very ambitious scheme of Government of India which is targeted exclusively at girls of disadvantaged sections of the educationally backward areas of the country. This research paper is an attempt to assess the achievement level of students of KGBVs and the physical infrastructure available to them.